2019
DOI: 10.1186/s12920-019-0472-0
|View full text |Cite
|
Sign up to set email alerts
|

Identification of long non-coding RNA-related and –coexpressed mRNA biomarkers for hepatocellular carcinoma

Abstract: BackgroundWhile changes in mRNA expression during tumorigenesis have been used widely as molecular biomarkers for the diagnosis of a number of cancers, the approach has limitations. For example, traditional methods do not consider the regulatory and positional relationship between mRNA and lncRNA. The latter has been largely shown to possess tumor suppressive or oncogenic properties. The combined analysis of mRNA and lncRNA is likely to facilitate the identification of biomarkers with higher confidence.Results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…Transcription and dysfunction of lncRNA is closely involved in tumorigenesis, including HCC [ 22 ]. Moreover, lncRNA with time and tissue specificity shows different expression levels in tumors and healthy states and different tumor stages, which suggests lncRNA has great potential to be a new prognostic biomarker [ 23 ]. For example, a controlled study involving 80 HCC patients and 50 healthy subjects finds that the expression of cancer susceptibility candidate 9 in HCC patients significantly increases with area under the curve (AUC) at 0.933 [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Transcription and dysfunction of lncRNA is closely involved in tumorigenesis, including HCC [ 22 ]. Moreover, lncRNA with time and tissue specificity shows different expression levels in tumors and healthy states and different tumor stages, which suggests lncRNA has great potential to be a new prognostic biomarker [ 23 ]. For example, a controlled study involving 80 HCC patients and 50 healthy subjects finds that the expression of cancer susceptibility candidate 9 in HCC patients significantly increases with area under the curve (AUC) at 0.933 [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…The modifications in the condition of the liver all over the formation of hepatocellular carcinoma are supported by altering the tumor microenvironment (TME) form that continues an opportunity advocating malignancy. The modification of the signaling pathways is general in hepatocellular carcinoma and is important for the development of the malignancy [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, in the present study, low expression of MAPT-AS1 was associated with poor prognosis after nephrectomy in silico analysis. Several studies have found that integrated mRNA and lncRNA expression profiling are promising prognostic biomarkers in some cancers [31,32]. Collectively, these results indicate that MAPT and MAPT-AS1 would help to make promising prognostic biomarkers in ccRCC by integrating mRNA and lncRNA expression.…”
Section: Discussionmentioning
confidence: 88%